ANALISIS TINGKAT KEMAMPUAN MEMBACA PERMULAAN BAGI PESERTA DIDIK KELAS I SD N 38 LUBUKLINGGAU DENGAN MENGGUNAKAN MODEL PEMBELAJARAN SCRAMBEL - Dwi Meyvasari; Malika Ramadanti; Episiasi (CV. ADIBA ASIHA AMIRA, 2025)
This research aims to see the level of initial reading ability for class I students at SD Negeri 38 Lubuklinggau using the Scramble learning model in Lesson B. Indonesia. This type of research is qualitative research with a population and sample of class I students at SD Negeri 38 Lubuklinggau, namely a population of 49 students and a sample taken from class IA totaling 24 students. The data collection techniques used were observation techniques, teacher interviews and documentation. The results of this research show an increase in initial reading ability using the Scramble learning model.